Spatial Quality as a decisive criterion in flood risk strategies - Anne Loes Nillesen (A+BE: Architecture and the Built Environment)
The role of the designer in flood risk management strategy development is currently often restricted to the important but limited task of optimally embedding technical interventions, which are themselves derivatives of system level flood risk strategies that are developed at an earlier stage, in their local surroundings. During this thesis research, an integrated approach is developed in which spatial quality can already be included in the regional flood risk management strategy development and thus can become a decisive ‘ex-ante’ aspect of flood risk management strategy development.